PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN DEBT TO EQUITY RATIO TERHADAP PROFITABILITAS PADA PERUSAHAAN SEKTOR PERTAMBANGAN DI BEI TAHUN 2020-2024 - Rahmiati Rahmiati; Arnadi Chairunnas; Surianto Ilham (Komunitas Manajemen Kompetitif, 2026)
The Effect of Corporate Social Responsibility (CSR) and Debt to Equity Ratio (DER) on Profitability in Mining Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the Period 2020–2024This research employs a quantitative approach with an associative research design. The data used are secondary data in the form of financial statements of mining sector companies listed on the IDX during 2020–2024. The sample consists of 8 companies with a total of 40 observations selected using purposive sampling technique. The data were analyzed using multiple linear regression analysis with the assistance of SPSS version 29. The results show that partially, Corporate Social Responsibility (CSR) does not have a significant effect on profitability with a significance value of 0.729 (> 0.05). Meanwhile, Debt to Equity Ratio (DER) has a significant effect on profitability with a significance value of 0.029 (< 0.05). However, simultaneously, Corporate Social Responsibility (CSR) and Debt to Equity Ratio (DER) do not have a significant effect on profitability, as indicated by a significance value of 0.720 (> 0.05). The R value of 0.256 indicates a weak relationship between the independent variables and profitability. The R Square value of 0.065 indicates that Corporate Social Responsibility (CSR) and Debt to Equity Ratio (DER) together explain only 6.5% of the variation in profitability, while the remaining 93.5% is influenced by other variables outside this study Keywords: Corporate Social Responsibility (CSR), Debt to Equity Ratio (DER), Profitability, Mining Companies.